Differential Expression of Serum Exosomal miRNAs in Breast CancerPatients and Healthy Controls - Rahim Asgari; Jafar Rezaie (Tabriz University of Medical Sciences, 2022)
Purpose: Breast cancer has become as a serious public health concern worldwide. Breastcancer cells release exosomes into the circulatory system, which are easily accessible for furtheranalysis like cancer diagnosis. In this study, we aimed to investigate expression of circulatingexosomal miRNAs (miRs) in the serum of individuals with breast cancer and healthy controls.Methods: Exosomes were collected from serum samples using a commercial kit and characterizedby scanning electron microscopy (SEM) and flow cytometry analysis. Expression of miRs suchas miR-21, miR-155, miR-182, miR-373, and miR-126 were evaluated by real-time PCR.Results: The result showed that the expression level of exosomal miR-21, miR-155, miR-182, and miR-373 in the serum of breast cancer patients was higher than of those controls(P<0.05). However, expression of miR-126 did not change between breast cancer and controlindividuals (P > 0.05).Conclusion: Our results showed a different miRs expression pattern between breast cancer andhealthy samples, supposing potential biomarkers for breast cancer. Further studies focusing onthese miRs are required to confirm our findings.